J. Scott Kennedy, J. H. Birnie, G. Ansre: "A Bilingual Approach to Theatre Development in Ghana". Proceedings of the Conference on "The Study of Ghanaian Languages" - Uribe-Villegas, Oscar (Revista Mexicana de Sociología, 2024)
-